A composite negative electrode material and its preparation method and application

By introducing cation coordination into black phosphorus and combining with conductive carbon black and binder, composite negative electrode materials are prepared, which solves the problems of volume changes in black phosphorus and unstable kinetic performance, and achieves higher electrochemical stability and safety.

CN118281153BActive Publication Date: 2025-03-21CHENGDU TECH UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410710713.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-04
Publication Date
2025-03-21
Estimated Expiration
2044-06-04

AI Technical Summary

Technical Problem

As an anode material, black phosphorus has problems such as large volume changes, edge atom reconstruction and unstable kinetic performance, which limits its application in lithium-ion batteries.

Method used

A composite negative electrode material is prepared by introducing cationic coordination into black phosphorus to form cationic coordination black phosphorus and combining it with conductive carbon black and binder. The material diffuses cations between the black phosphorus layer, providing stable support, avoiding edge reconstruction, and improving ion transport kinetics.

Benefits of technology

The composite anode material avoids volume changes during charging and discharging, improves electrochemical stability and service life, enhances safety, and maintains stable electrochemical properties while meeting higher specific capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118281153B_ABST
    Figure CN118281153B_ABST
Patent Text Reader

Abstract

The invention discloses a composite negative electrode material and a preparation method and application thereof, which relate to the technical field of battery materials and solve the technical problems of large volume change and unstable kinetic performance of existing black phosphorus negative electrode materials. The composite negative electrode material of the invention comprises cation-coordinated black phosphorus, conductive carbon black and a binder, wherein the mass ratio of the cation-coordinated black phosphorus, the conductive carbon black and the binder is (6-8):(1-2):(1-2). In the cation-coordinated black phosphorus, cations diffuse between black phosphorus layers to provide stable support and channels for ion transmission. The composite negative electrode material of the invention can improve the electrochemical stability of the negative electrode, avoid volume change during charge and discharge, and improve service life and safety.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a composite negative electrode material and a preparation method and application thereof. Background Art

[0002] As the demand for the energy density of lithium batteries increases, lithium-ion batteries with graphite as the negative electrode have reached their theoretical limit and it is difficult to further increase the energy density. If black phosphorus lithium metal can replace graphite, it can greatly increase the energy density of the battery. However, the electrochemical behavior of lithium ions in the process of charging and discharging lithium metal is uncontrolled, and lithium dendrites are easily formed, resulting in a decrease in cycle life. As the dendrites grow, they may even puncture the diaphragm, causing a short circuit and safety problems. In addition, lithium metal is chemically active, and irreversible side reactions will occur when it comes into contact with the electrolyte, forming a solid electrolyte interface film (SEI film), which consumes precious electrolyte and lithium metal. In addition, lithium metal will produce volume changes during the charging and discharging process, causing pressure to form inside the battery during the charging and discharging process, affecting the battery's life and safety.

[0003] The theoretical specific capacity of black phosphorus is 2596 mAh / g, which is nearly 7 times that of graphite. However, each phosphorus atom in black phosphorus has a lone electron pair and is easily oxidized. In addition, the volume of black phosphorus changes greatly during the charge and discharge process, resulting in an unstable electrode / electrolyte interface. The atomic reconstruction at the edge of black phosphorus hinders the entry of lithium ions into black phosphorus, resulting in a decrease in kinetic performance. Therefore, the above properties of black phosphorus limit its application as a negative electrode material. Summary of the invention

[0004] The present invention aims to solve the technical problems of large volume change, edge atomic reconstruction and unstable kinetic performance of black phosphorus as a negative electrode material. The present invention aims to provide a composite negative electrode material and its preparation method and application, which can improve the electrochemical stability of the negative electrode, avoid volume change during charging and discharging, and improve service life and safety.

[0005] The present invention is achieved through the following technical solutions:

[0006] The first object of the present invention is to provide a composite negative electrode material, comprising cation-coordinated black phosphorus, conductive carbon black and a binder, wherein the mass ratio of the cation-coordinated black phosphorus, the conductive carbon black and the binder is (6~8):(1~2):(1~2), and in the cation-coordinated black phosphorus, cations diffuse between black phosphorus layers to provide stable support and channels for ion transmission.

[0007] Black phosphorus has a layered structure. On the one hand, edge atomic reconstruction and structural deformation are prone to occur, thereby hindering the movement of ions. On the other hand, during the charge and discharge process, ions enter the black phosphorus layered structure, causing volume expansion. After the ions escape, the structure collapses, resulting in a large volume change. Based on this situation, the present invention modifies black phosphorus to expand the application of black phosphorus in negative electrode materials.

[0008] Under the action of chemical potential, the present invention causes cations to diffuse between black phosphorus layers to provide stable support, stabilize the layered structure of black phosphorus, and avoid reconstruction of the black phosphorus edge. In this way, during the charge and discharge process, on the one hand, since the black phosphorus layers are supported to form a stable ion transmission channel, ions are continuously embedded and released in the transmission channel without affecting the volume size, thereby avoiding volume changes during the charge and discharge process and improving service life and safety. On the other hand, since the coordination of the cations provides stable support between the black phosphorus layers, the stability of the black phosphorus structure can be improved, and the reconstruction of the black phosphorus edge can be effectively inhibited. After the cations enter, the interlayer distance of the black phosphorus is increased, which provides good kinetic conditions for ion diffusion and is more conducive to the transmission of lithium ions. While meeting a higher specific capacity, it can ensure that the composite negative electrode material has stable electrochemical properties.

[0009] As a further technical solution of the present invention, the binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber and polyurethane rubber.

[0010] As a further technical solution of the present invention, the cation is any one or more of copper ions, magnesium ions, sodium ions and silver ions.

[0011] The second object of the present invention is to provide a method for preparing a composite negative electrode material, comprising the following steps:

[0012] (1) dissolving an organic salt of a cation in an organic solvent to obtain a solution containing the organic salt;

[0013] (2) adding black phosphorus to the solution containing the organic salt obtained in step (1), and drying the solution to obtain copper ion or magnesium ion coordinated black phosphorus;

[0014] (3) mixing the copper ion or magnesium ion coordinated black phosphorus obtained in step (2) with conductive carbon black, grinding or stirring them evenly to obtain a mixture of cationic copper ion or magnesium ion coordinated black phosphorus and conductive carbon black;

[0015] (4) dissolving the binder in an organic solvent to form a solution containing the binder;

[0016] (5) adding the mixture of cationic copper ions or magnesium ions coordinated black phosphorus and conductive carbon black obtained in step (3) to the solution containing the binder obtained in step (4), and grinding or stirring to form a uniform slurry;

[0017] (6) The slurry obtained in step (5) is evenly applied to the substrate and dried to form a thin film on the substrate, thereby obtaining the composite negative electrode material.

[0018] As a further technical solution of the present invention, the organic salt of the cation in step (1) is selected from any one or more of acetate, propionate, hexanoate, pamoate, cyclopentanepropionate, adipate, alginate, aspartate, benzoate, citrate, oxalate, succinate, tartrate, lactate, maleate, fumarate, camphorate, nicotinate, pectinate, picrate, pivalate, toluenesulfonate, gluconate, digluconate, hemisulfate, methanesulfonate, ethanesulfonate, 2-hydroxyethanesulfonate, dodecyl sulfate, camphorsulfonate, benzenesulfonate, 2-naphthalenesulfonate, thiocyanate, and phosphate; and the cation is any one or more of copper ion, magnesium ion, sodium ion, and silver ion.

[0019] As a further technical solution of the present invention, the organic solvent in step (1) is N,N-dimethylformamide solution.

[0020] As a further technical solution of the present invention, in step (2) and step (6), the drying process is: first drying at a temperature of 70-90° C. for 10-15 hours, and then drying in a vacuum at a temperature of 70-90° C. for 20-28 hours.

[0021] As a further technical solution of the present invention, in step (4), the organic solvent is NMP solution.

[0022] As a further technical solution of the present invention, the mass ratio of the cationic coordinated black phosphorus, the conductive carbon black and the binder is (6~8):(1~2):(1~2).

[0023] The third object of the present invention is to provide an application of a composite negative electrode material in a lithium ion battery or a sodium ion battery.

[0024] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0025] Under the action of chemical potential, the present invention causes cations to diffuse between black phosphorus layers to provide stable support, stabilize the layered structure of black phosphorus, and avoid reconstruction of the black phosphorus edge. In this way, during the charge and discharge process, on the one hand, since the black phosphorus layers are supported to form a stable ion transmission channel, ions are continuously embedded and released in the transmission channel without affecting the volume size, thereby avoiding volume changes during the charge and discharge process and improving service life and safety. On the other hand, since the coordination of the cations provides stable support between the black phosphorus layers, the stability of the black phosphorus structure can be improved, and the reconstruction of the black phosphorus edge can be effectively inhibited. After the cations enter, the interlayer distance of the black phosphorus is increased, which provides good kinetic conditions for ion diffusion and is more conducive to the transmission of lithium ions. While meeting a higher specific capacity, it can ensure that the composite negative electrode material has stable electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0027] Figure 1 The composite negative electrode composed of black phosphorus coordinated with magnesium ions, carbon black and PVDF in Example 1 is 1 mA / cm 2 At a current density of 1 mAh / cm 2 Constant current test diagram under surface capacity;

[0028] Figure 2 The composite negative electrode composed of uncoordinated black phosphorus, carbon black and PVDF is compared at 1 mA / cm 2 At a current density of 1 mAh / cm 2 Constant current test diagram under surface capacity;

[0029] Figure 3 The composite negative electrode composed of black phosphorus coordinated by copper ions, carbon black and PVDF in Example 2 is 5 mA / cm 2 At a current density of 5 mAh / cm 2 Constant current test diagram under surface capacity;

[0030] Figure 4 The composite negative electrode composed of uncoordinated black phosphorus, carbon black and PVDF is compared at 5 mA / cm 2 At a current density of 5 mAh / cm 2 Constant current test diagram under surface capacity. DETAILED DESCRIPTION

[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0032] Example 1

[0033] This embodiment provides a method for preparing a composite negative electrode material, comprising the following steps:

[0034] (1) Dissolve 8 mg of magnesium acetate in 80 mL of N,N-dimethylformamide (DMF) solution to obtain a DMF solution with a magnesium acetate concentration of 0.1 mg / mL;

[0035] (2) adding 80 mg of black phosphorus to the DMF solution with a magnesium acetate concentration of 0.1 mg / mL obtained in step (1), then drying at 80° C. for 12 hours, and then drying in a vacuum at 80° C. for 24 hours to obtain magnesium ion coordinated black phosphorus;

[0036] (3) mixing the magnesium ion coordinated black phosphorus obtained in step (2) with the conductive carbon black in a mass ratio of 8:1, grinding or stirring to obtain a mixture of magnesium ion coordinated black phosphorus and conductive carbon black;

[0037] (4) Dissolve 10 mg of PVDF (binder) powder in 2 mL of NMP solution to form an NMP solution with a PVDF concentration of 5 mg / mL;

[0038] (5) adding the mixture of magnesium ion coordinated black phosphorus and conductive carbon black obtained in step (3) to the NMP solution with a PVDF concentration of 5 mg / mL obtained in step (4), and grinding or stirring for several hours to form a uniform slurry;

[0039] (6) The slurry obtained in step (5) is evenly applied to a magnesium foil, and then dried at 80° C. for 12 hours to volatilize the NMP solution, and then dried at 80° C. in a vacuum for another 24 hours to form a thin film on the magnesium foil;

[0040] (7) Cutting the film obtained in step (6) into a pole piece shape to obtain a composite negative electrode material.

[0041] The composite negative electrode material prepared in this embodiment is magnesium ion coordinated black phosphorus, conductive carbon black and PVDF, and the mass ratio of magnesium ion coordinated black phosphorus, conductive carbon black and PVDF is 8:1:1.

[0042] Example 2

[0043] This embodiment provides a method for preparing a composite negative electrode material, comprising the following steps:

[0044] (1) Dissolve 8 mg of copper acetate in 80 mL of N,N-dimethylformamide (DMF) solution to obtain a DMF solution with a copper acetate concentration of 0.1 mg / mL;

[0045] (2) adding 80 mg of black phosphorus to the DMF solution with a copper acetate concentration of 0.1 mg / mL obtained in step (1), then drying at 80° C. for 12 hours, and then drying in a vacuum at 80° C. for 24 hours to obtain magnesium ion coordinated black phosphorus;

[0046] (3) mixing the magnesium ion coordinated black phosphorus obtained in step (2) with the conductive carbon black in a mass ratio of 8:1, grinding or stirring them evenly to obtain a mixture of copper ion coordinated black phosphorus and conductive carbon black;

[0047] (4) Dissolve 10 mg of PVDF (binder) powder in 2 mL of NMP solution to form an NMP solution with a PVDF concentration of 5 mg / mL;

[0048] (5) adding the mixture of copper ion coordinated black phosphorus and conductive carbon black obtained in step (3) to the NMP solution with a PVDF concentration of 5 mg / mL obtained in step (4), and grinding or stirring for several hours to form a uniform slurry;

[0049] (6) The slurry obtained in step (5) is evenly applied to a magnesium foil, and then dried at 80° C. for 12 hours to volatilize the NMP solution, and then dried at 80° C. in a vacuum for another 24 hours to form a thin film on the magnesium foil;

[0050] (7) Cutting the film obtained in step (6) into a pole piece shape to obtain a composite negative electrode material.

[0051] The composite negative electrode material prepared in this embodiment is copper ion coordinated black phosphorus, conductive carbon black and PVDF, and the mass ratio of copper ion coordinated black phosphorus, conductive carbon black and PVDF is 8:1:1.

[0052] Example 3

[0053] This embodiment provides a method for preparing a composite negative electrode material, comprising the following steps:

[0054] (1) Dissolve 8 mg of magnesium acetate in 80 mL of N,N-dimethylformamide (DMF) solution to obtain a DMF solution with a magnesium acetate concentration of 0.1 mg / mL;

[0055] (2) adding 70 mg of black phosphorus to the DMF solution with a magnesium acetate concentration of 0.1 mg / mL obtained in step (1), then drying at 80° C. for 12 hours, and then drying in a vacuum at 80° C. for 24 hours to obtain magnesium ion coordinated black phosphorus;

[0056] (3) mixing the magnesium ion coordinated black phosphorus obtained in step (2) with the conductive carbon black in a mass ratio of 7:2, grinding or stirring them evenly to obtain a mixture of magnesium ion coordinated black phosphorus and conductive carbon black;

[0057] (4) Dissolve 10 mg of PVDF (binder) powder in 2 mL of NMP solution to form an NMP solution with a PVDF concentration of 5 mg / mL;

[0058] (5) adding the mixture of magnesium ion coordinated black phosphorus and conductive carbon black obtained in step (3) to the NMP solution with a PVDF concentration of 5 mg / mL obtained in step (4), and grinding or stirring for several hours to form a uniform slurry;

[0059] (6) The slurry obtained in step (5) is evenly applied to a magnesium foil, and then dried at 80° C. for 12 hours to volatilize the NMP solution, and then dried at 80° C. in a vacuum for another 24 hours to form a thin film on the magnesium foil;

[0060] (7) Cutting the film obtained in step (6) into a pole piece shape to obtain a composite negative electrode material.

[0061] The composite negative electrode material prepared in this embodiment is magnesium ion coordinated black phosphorus, conductive carbon black and PVDF, and the mass ratio of magnesium ion coordinated black phosphorus, conductive carbon black and PVDF is 7:2:1.

[0062] Example 4

[0063] This embodiment provides a method for preparing a composite negative electrode material, comprising the following steps:

[0064] (1) Dissolve 8 mg of magnesium acetate in 80 mL of N,N-dimethylformamide (DMF) solution to obtain a DMF solution with a magnesium acetate concentration of 0.1 mg / mL;

[0065] (2) adding 70 mg of black phosphorus to the DMF solution with a magnesium acetate concentration of 0.1 mg / mL obtained in step (1), then drying at 80° C. for 12 hours, and then drying in a vacuum at 80° C. for 24 hours to obtain magnesium ion coordinated black phosphorus;

[0066] (3) mixing the magnesium ion coordinated black phosphorus obtained in step (2) with the conductive carbon black in a mass ratio of 7:1, grinding or stirring evenly to obtain a mixture of magnesium ion coordinated black phosphorus and conductive carbon black;

[0067] (4) Dissolve 20 mg of PVDF (binder) powder in 2 mL of NMP solution to form an NMP solution with a PVDF concentration of 10 mg / mL;

[0068] (5) adding the mixture of magnesium ion coordinated black phosphorus and conductive carbon black obtained in step (3) to the NMP solution with a PVDF concentration of 5 mg / mL obtained in step (4), and grinding or stirring for several hours to form a uniform slurry;

[0069] (6) The slurry obtained in step (5) is evenly applied to a magnesium foil, and then dried at 80° C. for 12 hours to volatilize the NMP solution, and then dried at 80° C. in a vacuum for another 24 hours to form a thin film on the magnesium foil;

[0070] (7) Cutting the film obtained in step (6) into a pole piece shape to obtain a composite negative electrode material.

[0071] The composite negative electrode material prepared in this embodiment is magnesium ion coordinated black phosphorus, conductive carbon black and PVDF, and the mass ratio of magnesium ion coordinated black phosphorus, conductive carbon black and PVDF is 7:1:2.

[0072] Example 5

[0073] This embodiment provides a method for preparing a composite negative electrode material, comprising the following steps:

[0074] (1) Dissolve 8 mg of magnesium acetate in 80 mL of N,N-dimethylformamide (DMF) solution to obtain a DMF solution with a magnesium acetate concentration of 0.1 mg / mL;

[0075] (2) adding 60 mg of black phosphorus to the DMF solution with a magnesium acetate concentration of 0.1 mg / mL obtained in step (1), then drying at 80° C. for 12 hours, and then drying in a vacuum at 80° C. for 24 hours to obtain magnesium ion coordinated black phosphorus;

[0076] (3) mixing the magnesium ion coordinated black phosphorus obtained in step (2) with the conductive carbon black in a mass ratio of 6:2, grinding or stirring to obtain a mixture of magnesium ion coordinated black phosphorus and conductive carbon black;

[0077] (4) Dissolve 20 mg of PVDF (binder) powder in 2 mL of NMP solution to form an NMP solution with a PVDF concentration of 10 mg / mL;

[0078] (5) adding the mixture of magnesium ion coordinated black phosphorus and conductive carbon black obtained in step (3) to the NMP solution with a PVDF concentration of 5 mg / mL obtained in step (4), and grinding or stirring for several hours to form a uniform slurry;

[0079] (6) The slurry obtained in step (5) is evenly applied to a magnesium foil, and then dried at 80° C. for 12 hours to volatilize the NMP solution, and then dried at 80° C. in a vacuum for another 24 hours to form a thin film on the magnesium foil;

[0080] (7) Cutting the film obtained in step (6) into a pole piece shape to obtain a composite negative electrode material.

[0081] The composite negative electrode material prepared in this embodiment is magnesium ion coordinated black phosphorus, conductive carbon black and PVDF, and the mass ratio of magnesium ion coordinated black phosphorus, conductive carbon black and PVDF is 6:2:2.

[0082] Comparative Example: The difference between this comparative example and Example 1 is that steps (1) and (2) are omitted, and black phosphorus is used directly without cationic coordination treatment.

[0083] The following are the relevant performance test data of Example 1, Example 2 and the comparative example.

[0084] Figure 1 The composite negative electrode composed of black phosphorus coordinated with magnesium ions, carbon black and PVDF in Example 1 is 1 mA / cm 2 At a current density of 1 mAh / cm 2 Constant current test diagram under surface capacity.

[0085] Figure 2 The composite negative electrode composed of uncoordinated black phosphorus, carbon black and PVDF is compared at 1 mA / cm 2 At a current density of 1 mAh / cm 2 Constant current test diagram under surface capacity.

[0086] contrast Figure 1 and 2 It can be seen that at 1 mA / cm 2 At a current density of 1 mAh / cm 2Under the surface capacity, the polarization voltage of the composite negative electrode composed of black phosphorus coordinated by magnesium ions, carbon black and PVDF is only about 0.01V, and it can be stably cycled for 1600 hours with stable voltage. The polarization voltage of the composite negative electrode composed of uncoordinated black phosphorus, carbon black and PVDF is about 0.05V at the beginning. As the cycle proceeds, the voltage gradually increases and the kinetic performance deteriorates. This is mainly because the black phosphorus coordinated by magnesium ions effectively inhibits the atomic reconstruction of the edge of black phosphorus, and the coordination of magnesium ions increases the interlayer spacing of black phosphorus, which is more conducive to the transmission of ions and provides good kinetic conditions for ion diffusion, so that the negative electrode has stable electrochemical properties.

[0087] Figure 3 The composite negative electrode composed of black phosphorus coordinated by copper ions, carbon black and PVDF in Example 2 is 5 mA / cm 2 At a current density of 5 mAh / cm 2 Constant current test diagram under surface capacity.

[0088] Figure 4 The composite negative electrode composed of uncoordinated black phosphorus, carbon black and PVDF is compared at 5 mA / cm 2 At a current density of 5 mAh / cm 2 Constant current test diagram under surface capacity.

[0089] contrast Figure 3 and 4 It can be seen that at 5 mA / cm 2 At a current density of 5 mAh / cm 2 Under the surface capacity, the polarization voltage of the composite negative electrode composed of black phosphorus coordinated by copper ions, carbon black and PVDF can remain stable within 1500 hours, and is only about 0.08V, while the polarization voltage of the composite negative electrode composed of uncoordinated black phosphorus, carbon black and PVDF gradually increases with the progress of the cycle, from the initial about 0.12V to about 0.7V, which is much larger than the internal resistance of the composite negative electrode composed of copper coordinated black phosphorus, carbon black and PVDF. This shows that the application of copper coordinated black phosphorus in negative electrode materials does improve the kinetic performance of the negative electrode.

[0090] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a composite negative electrode material, characterized in that: The composite negative electrode material comprises cation-coordinated black phosphorus, conductive carbon black and a binder, wherein the mass ratio of the cation-coordinated black phosphorus, the conductive carbon black and the binder is (6-8):(1-2):(1-2), and in the cation-coordinated black phosphorus, cations diffuse between black phosphorus layers to provide stable support and channels for ion transmission; The binder is any one of polyvinylidene fluoride, polytetrafluoroethylene, styrene-butadiene rubber and polyurethane rubber; The cation is any one or more of copper ion, magnesium ion, sodium ion and silver ion; The method for preparing the composite negative electrode material comprises the following steps: (1) dissolving an organic salt of a cation in an organic solvent to obtain a solution containing the organic salt; (2) adding black phosphorus to the solution containing the organic salt obtained in step (1), and drying the solution to obtain cationic coordinated black phosphorus; (3) mixing the copper ion- or magnesium ion-coordinated black phosphorus obtained in step (2) with conductive carbon black, grinding or stirring them evenly to obtain a mixture of cation-coordinated black phosphorus and conductive carbon black; (4) dissolving the binder in an organic solvent to form a solution containing the binder; (5) adding the mixture of the cationic coordinated black phosphorus and the conductive carbon black obtained in step (3) to the solution containing the binder obtained in step (4), and grinding or stirring to form a uniform slurry; (6) The slurry obtained in step (5) is evenly applied to a substrate, and dried to form a thin film on the substrate, thereby obtaining the composite negative electrode material; In step (2) and step (6), the drying process is: first drying at a temperature of 70 to 90° C. for 10 to 15 hours, and then drying in a vacuum at a temperature of 70 to 90° C. for 20 to 28 hours.

2. The method for preparing a composite negative electrode material according to claim 1, characterized in that: The organic salt of the cation in step (1) is selected from any one or more of acetate, propionate, hexanoate, pamoate, cyclopentanepropionate, adipate, alginate, aspartate, benzoate, citrate, oxalate, succinate, tartrate, lactate, maleate, fumarate, camphorate, nicotinate, pectinate, picrate, pivalate, toluenesulfonate, gluconate, digluconate, hemisulfate, methanesulfonate, ethanesulfonate, 2-hydroxyethanesulfonate, dodecyl sulfate, camphorsulfonate, benzenesulfonate, 2-naphthalenesulfonate, thiocyanate, and phosphate; and the cation is any one or more of copper ion, magnesium ion, sodium ion, and silver ion.

3. The method for preparing a composite negative electrode material according to claim 1, characterized in that: The organic solvent in step (1) is N,N-dimethylformamide solution.

4. The method for preparing a composite negative electrode material according to claim 1, characterized in that: In step (4), the organic solvent is NMP solution.

5. Use of a composite negative electrode material prepared by the preparation method according to any one of claims 1 to 4 in a lithium ion battery or a sodium ion battery.

Citation Information

Patent Citations

  • Metal ion modified black phosphorus as well as preparation method and application of metal ion modified black phosphorus

    CN106185848A